Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-1998 Volume II Government of Kerala - Planning Commission (Planning Commission, 1997)
Draft Ninth Plan (1997-2002) and Annual Plan - 1997-1998 - Outlays Physical Targets and Achievements A Draft Plan (1997-2002) Proposals for Spill over and ongoing Programmes/Projects as in Annexure-I Draft Ninth Plan (1997-2002) Proposals for Maximising Benefits of completed Programmes/Projects (As on 31-3-1997) Draft Ninth Plan (1397 - 2002) Proposals for Programmes/Projects - New Schemes Summary Statement - Draft Ninth Plan 1997-2002) - Proposals for Programmes/Projects Statement Regarding Externally Aided Projects Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 outlays - By heads of Development - for District Plans Centrally Sponsored Schemes A Draft Ninth plan (1987-2002) and Annual Plan - 1997-98 Basic Minimum Services - Outlay/Expenditure.
Government of Kerala, State Planning Board